A Literature Review on Virtual Reality Study in EFL Context - Sylvia (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This literature review investigates how Virtual Reality (VR) is implemented and how it impacts learning in the context of English as a Foreign Language (EFL). With the advancement of immersive technologies, Virtual Reality (VR) has become a promising tool to foster language learning by providing engaging, authentic and interactive environments. This review scrutinizes research studied in 2025, 2024, 2023 and 2022 that explores the utilizing of VR in boosting different language skills, including listening, speaking and writing. The findings indicate that immersive technologies such as VR, AR, and AI significantly enhance EFL learners’ language proficiency, critical thinking, motivation, and transferable 21st-century skills. Yet, the review also points out several challenges, such as limited resources, large class sizes, insufficient institutional support, teachers’ low TPACK, short VR exposure time, lack of scaffolding, low realism and interactivity in VR content, occurrences of cybersickness, and the limited scope of studies. Future research should adopt rigorous experimental designs, explore underrepresented language skills, examine affective and contextual factors, and prioritize teacher professional development to ensure effective, inclusive, and sustainable integration of immersive VR in EFL instruction.